Corporate environmental management information systems advancements and trends - Teuteberg, Frank 1970-; Marx Gómez, Jorge Carlos 1960- (Business Science Reference, 2010)
"This book summarizes the state of the art in the emergent field of Corporate Environmental Management Information Systems, showing researchers, managers, engineers and information technology specialists how to develop and implement effective CEMIS" - Provided by publisher
Includes bibliographical references and index
Keywords: Umweltschutz; Environmental protection / Citizen participation; Environmental protection / Information services; Managementinformationssystem; Aufsatzsammlung